Pemanfaatan Limbah Kulit Nanas untuk Pembuatan Produk Nata De Pina Menggunakan Metode Eksperimen Taguchi - Ismu Kusumanto (Kutubkhanah, 2013)
Waste generated in the form of a pineapple skin in a state containing water, in a relatively short time the waste with a mixture of other wastes such as tubers will rot, it can cause adverse effects to the environment. Therefore, the skin of the pineapple production waste should be processed into an economically valuable product. Products that will be made is a nata. This product is produced from the fermentation process of the bacteria Acetobacter xylinum by doing experiments. From the analysis it can be concluded that the skin of the skin then blended with water to the skin produces a rich pineapple juice then for one kilo of medium skin produce 2 liters of water that has been mixed nata. The media is what will be the growth of bacteria Acetobacter xylinum are undergoing a process of fermentation and then became nata.